2021
DOI: 10.3389/fonc.2021.555277
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectric Impedance Analysis Test Improves the Detection of Prostate Cancer in Biopsy Candidates: A Multifeature Decision Support System

Abstract: Prostate cancer (PCa) gold-standard diagnosis relies on prostate biopsy, which is currently overly recommended since other available noninvasive tools such as prostate-specific antigen (PSA) multiparametric MRI (mMRI) showed low diagnostic accuracy or high costs, respectively. The aim of the study was to determine the accuracy of a novel Bioelectric Impedance Analysis (BIA) test endorectal probe for the selection of patients candidate to prostate biopsy and in particular the clinical value of three different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Two studies explored the effectiveness of localized BIA and its PhA as a screening and prognostic tool for patients with prostate cancer [ 103 , 104 ]. Tyagi et al demonstrated that low PhA allowed discriminating prostate cancer patients using BIA electrodes on the right upper and right lower limb and a multifrequency BIA (QuadScan 4000 (Bodystat®; Isle of Man) [ 103 ].…”
Section: Other Applications / Segmental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies explored the effectiveness of localized BIA and its PhA as a screening and prognostic tool for patients with prostate cancer [ 103 , 104 ]. Tyagi et al demonstrated that low PhA allowed discriminating prostate cancer patients using BIA electrodes on the right upper and right lower limb and a multifrequency BIA (QuadScan 4000 (Bodystat®; Isle of Man) [ 103 ].…”
Section: Other Applications / Segmental Analysismentioning
confidence: 99%
“…In the other study, four electrodes were placed around the prostate area and a single frequency BIA (BIA 101 ASE®; Akern Srl, Italy) was used to measure PhA values in individuals with prostate cancer, benign prostatic disease, and healthy volunteers. Although Xc and R values differed between studied groups, PhA had a good sensitivity (0.925) but a poor specificity (0.200) to diagnose patients with prostate cancer [ 104 ]. Although none of these studies have evaluated the presence of inflammation, it is well known that the inflammatory state is associated with cancer, muscle damage and wound healing [ 3 , 105 , 106 ].…”
Section: Other Applications / Segmental Analysismentioning
confidence: 99%